2004
DOI: 10.1177/070674370404900807
|View full text |Cite
|
Sign up to set email alerts
|

Selective Serotonin Reuptake Inhibitor and Venlafaxine Use in Children and Adolescents with Major Depressive Disorder: A Systematic Review of Published Randomized Controlled Trials

Abstract: Objective: This review critiques published randomized placebo-controlled trials pertaining to the efficacy and safety of selective serotonin reuptake inhibitors (SSRIs) and venlafaxine in the treatment of major depressive disorder in children and adolescents. Method:Medline was searched for articles meeting defined inclusion criteria. The following key terms were used: depressive disorders, antidepressive agents, fluoxetine, paroxetine, sertraline, citalopram, fluvoxamine, venlafaxine, child, and adolescent.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…They concluded that a large benefit from newer antidepressant drugs is unlikely. Reviewing the same studies, another report judged the efficacy data to be inconclusive [53]. …”
Section: Different Reviews Have Had Different Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that a large benefit from newer antidepressant drugs is unlikely. Reviewing the same studies, another report judged the efficacy data to be inconclusive [53]. …”
Section: Different Reviews Have Had Different Resultsmentioning
confidence: 99%
“…Since the above reviews [52,53] included in their analysis a negative study of fluoxetine which involved a small (n = 30), clinically heterogeneous (mixed inpatients and outpatients) participant group [39], some later reviews opted to exclude this negative study from their analyses. For example, one study analyzed five of the six published papers addressed in the above-mentioned reviews [52,53], as well as data from six unpublished studies accessed through collaboration with the UK's MHRA [50].…”
Section: Different Reviews Have Had Different Resultsmentioning
confidence: 99%
“…18,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Tricyclic antidepressants are ineffective in children and have limited effectiveness in adolescents, with safety concerns in both groups. 18,40,41 There also is limited evidence for the effectiveness of selective serotonin reuptake inhibitors (SSRIs).…”
Section: Antidepressantsmentioning
confidence: 99%
“…Furthermore, there are high placebo response rates and methodologic flaws in studies supporting SSRI use. 43,52 For example, although one study indicated that fluoxetine plus cognitive behavior therapy was the best choice, the success of fluoxetine was found only in the unblinded arms of the study: the blinded arms showed no better response than with placebo. 39 Finally, most studies are underpowered to address the outcome of suicide.…”
Section: Antidepressantsmentioning
confidence: 99%
“…However, not only adults suffer from depression: estimations of the prevalence of depression amongst adolescents range between 1% and 25% (Kessler et al, 2001;van Dulmen et al, 2002). Consequently, SSRIs are often prescribed to children and adolescents, despite a lack of demonstrated efficacy and safety data in this subgroup (Courtney, 2004;Lynch et al, 2001;Murray et al, 2004;Rushton et al, 2000). Besides the risk of side effects caused by SSRIs during treatment in adolescents (Wilnes et al, 2003), SSRIs might also disturb the development of the central nervous system that is still proceeding during adolescence (Spear, 2000).…”
Section: Introductionmentioning
confidence: 99%